Development of the RPS Module in the Portal-Prodi System at the University of Lampung using the RAD Method - Pratama, Mahendra; Pramudya, Rivan Herdian; Muda, Mona Arif; Septama, Hery Dian (Universitas Negeri Semarang, 2024)
The development of the RPS Module in the University of Lampung Study Program Portal System aims to streamline and standardize the creation of Semester Learning Plans (RPS) in various study programs. In 2020, the ministry issued a policy ranking state universities based on key performance indicators (KPI). The KPI assessment has eight indicators, including KPI 7: Collaborative and Participatory Class. In this indicator, the Semester Learning Plan (RPS) is one of the main pieces of evidence for universities stating that lectures taught by lecturers are carried out using the Project Based Method or Case-Based Method. This research uses the Rapid Application Development (RAD) methodology. The iterative nature of the RAD method facilitates efficient requirements gathering, user design, construction, and implementation stages. The main features of the semester learning plan module have been successfully developed based on the features that have been created, namely, submitting RPS, validating RPS, viewing RPS, and printing RPS by generating RPS into a PDF file. Based on testing the semester learning plan module using the black box method, the test results followed the expected results and went well. This study contributes to ongoing efforts to integrate digital solutions in higher education administration.